Optimizing Discharge Planning to Enhance Caregiver Knowledge and Self‑Efficacy in Parents of Children with Cancer Undergoing Chemotherapy - Olivia Bawaeda; Allenidekania Allenidekania; Siti Chodidjah (FORIKES, 2026)
Childhood cancer poses significant challenges for families, particularly in settings where access to treatment and supportive care is limited. Children undergoing chemotherapy require repeated hospitalizations, creating disruptions in family routines and increasing caregiver burden. Discharge planning has been shown to strengthen caregiver readiness, improve continuity of care, and reduce unplanned visits. Knowledge and self‑efficacy are essential components of caregiver competence and influence decision‑making, adherence, and stress management. This study aimed to evaluate the effect of optimized discharge planning on caregiver knowledge and self‑efficacy among parents of children with cancer undergoing chemotherapy. A quantitative pre‑experimental one‑group pre‑posttest design was used involving 35 caregivers selected through purposive sampling. Researcher‑developed Guttman‑scale questionnaires measured knowledge (20 items) and self‑efficacy (25 items), both validated and reliable. The intervention consisted of structured discharge planning delivered from admission to discharge, including assessment, education on cancer, chemotherapy, and management of treatment side effects. Pre‑test data were collected at admission, and post‑test data at discharge. Analysis employed descriptive statistics and the Wilcoxon signed‑rank test. Results showed significant improvements in caregiver knowledge (mean increase from 76.28 to 81.57; p = 0.007) and self‑efficacy (mean increase from 70.40 to 80.91; p = 0.000). Gains were observed across all components of knowledge and self‑efficacy, and no respondent experienced a decline. In conclusion, optimized discharge planning effectively enhances caregiver knowledge and self‑efficacy in pediatric oncology settings, underscoring the importance of structured educational support during hospitalization and transition to home care.Keywords: childhood cancer; caregiver; discharge planning; knowledge; self‑efficacy; chemotherapy